Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/la051997s
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Tension and Electrocapillary Measurements of the Room Temperature Ionic Liquid/Aqueous Interface

Abstract: The surface and aqueous interfacial tensions for a series of water-immiscible room-temperature ionic liquids (RTILs) have been measured. The RTILs used in this study were based on 1-alkyl-3-methylimidazolium cations (Cnmim, n=6, 8, 10, and 12) and bis(perfluoromethylsulfonyl)imide (BMSI) and bis(perfluoroethylsulfonyl)imide (BETI) anions. It was found that the surface tensions of the RTILs increased with an increasing cation chain length similar to the behavior of n-alkanes. Interfacial tensions of the RTILs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
(89 reference statements)
1
37
0
Order By: Relevance
“…40,41 The resistance is independent of D w o f, whereas an increase in RC at positive and negative potential differences reects the increase of the capacitance with the polarisation of the interface. The RC time constant is a property of the interface and is not directly involved in the redox reactions; thus, the discussion will be limited to the other parameters.…”
Section: Intensity Modulated Photocurrent Spectroscopy (Imps)mentioning
confidence: 99%
“…40,41 The resistance is independent of D w o f, whereas an increase in RC at positive and negative potential differences reects the increase of the capacitance with the polarisation of the interface. The RC time constant is a property of the interface and is not directly involved in the redox reactions; thus, the discussion will be limited to the other parameters.…”
Section: Intensity Modulated Photocurrent Spectroscopy (Imps)mentioning
confidence: 99%
“…Methods for the determination of equilibrium thermodynamic and transport properties of ILs have been investigated both experimentally and theoretically [1][2][3]. Enthalpies of vaporization [4,5], viscosities [6], thermal conductivity [7], aggregation behavior [8], and liquid-liquid interfacial tension [9] of imidazolium-based ILs have been investigated widely. These ILs are also used in multiphase homogeneous catalysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] Local ion concentrations in EDLs are generally different from those in bulk. Electrocapillarity (dependence of surface tension on the phase-boundary potential) studies [44][45][46][47][48][49] at the IL|W interface confirmed fundamental features of the EDL such as surface excess and specific and non-specific adsorption of IL ions at the IL|W interface. These studies suggested that the EDL at the IL|W interface is not far from the view of the Gouy-Chapman-Stern model [50][51][52] that has long been the theoretical basis for EDL at the electrochemical interfaces such as electrode|electrolyte solution interface.…”
Section: Introductionmentioning
confidence: 70%